AB0905 Long-term (5-YEAR) efficacy and safety of apremilast monotherapy in dmard-naÏve subjects with active psoriatic arthritis. (12th June 2018) - Wells, A.F.; Edwards, C.J.; Kivitz, A.J.; Bird, P.; Guerette, B.; Delev, N.; Paris, M.; Teng, L.; Aelion, J.A.
Abstract : Background: Apremilast (APR) is an oral phosphodiesterase 4 inhibitor that helps regulate the immune responses that cause joint inflammation and other manifestations of psoriatic arthritis (PsA), including skin disease. Objectives: To describe the long-term (5 year) efficacy and safety of APR monotherapy in DMARD-naïve subjects with active PsA from the phase 3 PALACE 4 study. Methods: Subjects were randomised (1:1:1) to receive placebo, APR 30 mg BID (APR30), or APR 20 mg BID (APR20). At Week 16, subjects were eligible for early escape; placebo subjects were re-randomised to APR treatment, and APR subjects remained on their assigned dose. At Week 24, all subjects remaining on placebo were re-randomised to APR. Double-blind treatment continued to Week 52, with open-label APR treatment for up to 4 additional years. Results: A total of 527 subjects were randomised and received ≥1 dose of placebo (n=176), APR30 (n=176), or APR20 (n=175). Among subjects randomised to APR30 at baseline, 45.5% (80/176) completed the Week 260 visit. At Week 52, modified ACR20, ACR50, and ACR70 responses were achieved by 58.0%, 29.8%, and 15.5% of subjects receiving APR30, respectively, regardless of when APR was started (baseline, Week 16, or Week 24). Rates of improvement in PsA signs and symptoms and physical function were sustained up to Week 260 with continued APR30 treatment, including reduction rates in SJC of 84.8% and in TJC of 76.4% (table 1). At Week 260, 65.8%, 39.0%, and 20.3% of subjects achieved a modified ACR20, ACR50, and ACR70 response, respectively, and 71.2% of APR30 subjects with baseline enthesitis achieved a MASES of 0; 95.1% with baseline dactylitis achieved a dactylitis count of 0. At Week 260, 52.9% of subjects achieved a HAQ-DI MCID ≥0.35, 60.3% achieved a PASI-50 response, and 47.6% achieved a PASI-75 response (table 1). No new safety concerns were identified with APR up to 260 weeks. During Weeks>208 to≤260, the most common adverse event (AEs) among APR30-exposed subjects was nasopharyngitis (6.9%). Serious AEs occurred in 5 APR30 subjects; serious infections were reported in 2 APR30 subjects (pelvic abscess and bacterial urinary tract infection), and no opportunistic infections were reported during Weeks>208 to≤260. Conclusions: APR monotherapy demonstrated sustained response or improvements in PsA signs and symptoms, including SJC and TJC, enthesitis, dactylitis, physical function, and psoriasis in the population of subjects continuing treatment over 260 weeks. APR continued to demonstrate a favourable safety profile and was generally well tolerated. Disclosure of Interest: A. Wells Grant/research support from: Celgene Corporation, C. Edwards Grant/research support from: Celgene Corporation; Pfizer, Roche, Samsung, Consultant for: Celgene Corporation, Pfizer, Roche, Samsung, Speakers bureau: Abbott, GSK, Pfizer, Roche, A. Kivitz Consultant for: Celgene Corporation, Speakers bureau: Celgene Corporation, P. Bird Grant/research support from: Celgene Corporation, B. Guerette Employee of: Celgene Corporation, N. Delev Employee of: Celgene Corporation, M. Paris Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, J. Aelion Grant/research support from: Celgene Corporation; AbbVie, Ardea Biosciences, AstraZeneca, BMS, Centocor, Eli Lilly, Galápagos, Genentech, GSK, Human Genome Sciences, Janssen, Merck, Mesoblast, Novartis, Novo Nordisk, Pfizer, Roche, Sanofi-Aventis, Takeda Pharmaceuticals, UCB, Vertex Pharmaceuticals